Dental phenomics: advancing genotype to phenotype correlations in craniofacial research. (24th February 2014) - Yong, R; Ranjitkar, S; Townsend, GC; Smith, RN; Evans, AR; Hughes, TE; Lekkas, D; Brook, AH
Abstract: The field of dental phenomics provides many opportunities to elucidate the roles of genetic, epigenetic and environmental factors in craniofacial development. To date, research findings have helped to clarify the pathogenesis of many conditions, aiding diagnosis and clinical management. This paper provides an overview of dental phenomics research in some commonly encountered oral diseases in everyday clinical practice, as well as research relating to craniofacial growth and development. Clinically, advances in cariology and periodontology have led to better diagnostic capabilities and treatment provision. In the study of growth and development, important information regarding the varying clinical presentation and pathogenesis of many disorders is now apparent through the accurate quantification of phenotypes. Improvements in two‐dimensional (2D) and three‐dimensional (3D) imaging and analytical techniques have allowed for accurate dental phenotyping, and efforts are ongoing to apply these in vitro techniques to the in vivo setting. The field of dental phenomics represents an exciting avenue that links research findings to practical application, and collaboration between researcher and clinicians will help advance the field further.